Feeding ecology of the Stomiiformes (Pisces) of the northern Mid-Atlantic Ridge. 1. The Sternoptychidae and Phosichthyidae. (January 2015) - Carmo, Vanda; Sutton, Tracey; Menezes, Gui; Falkenhaug, Tone; Bergstad, Odd Aksel
Highlights: Diets of zooplanktivorous fishes of the northern Mid-Atlantic Ridge were examined. Two main patterns of feeding were detected: 1 – Copepod-eaters; 2 – Amphipod-eaters. Amphipods are reported as main prey for two species for the first time. Maurolicus diet mirrored phenotypic variation North and South the Subpolar Front. S. diaphana daily ration estimate was triple that of other midwater fishes. Abstract: Comprehensive trophic studies in the vast mid-oceanic regions are rare compared to coastal and fisheries-oriented investigations. Field sampling conducted by the multidisciplinary, international Census of Marine Life project MAR-ECO, namely the 2004 G . O . Sars cruise, has generated one of the largest open ocean deep-pelagic sample collections ever obtained. With the overall goal of understanding carbon flow processes within and through the deep-pelagic nekton associated with the northern Mid-Atlantic Ridge system (N MAR), quantitative trophic analyses were conducted in order to identify the major intraspecific patterns in diet of characteristic members of the midwater fish community. Diets of five abundant species of zooplanktivorous fishes were examined in detail in terms of prey taxonomy and variability in space, ontogeny and diel cycle. Two major patterns of feeding were identified. Pattern 1 included three species preying primarily on copepods, Argyropelecus hemigymnus, Maurolicus muelleri and Vinciguerria attenuata, the former two of which revealed spatial differences in diet with latitude, mostly likely related to latitudinal prey distributions and densities. Maurolicus demonstrated ecological differences in diet that mirrored phenotypic variation North and South of the Subpolar Front, an "oceanic species concept" question that warrants further research. Pattern 2 included two species feeding primarily on amphipods, Argyropelecus aculeatus and Sternoptyx diaphana, both of which showed ontogenetic variability in feeding primarily related to specific amphipod taxon sizes, rather than prey switching to other major prey taxa. This is the first study that highlights the importance of amphipods in the diets of these species. All fish species showed selectivity in prey choice, possibly related to competition with the other major nekton components along the N MAR, namely the Myctophidae and other zooplanktivorous Stomiiformes. Daily ration fell within the expected values for midwater fishes (1–4% of body weight) with the exception of S . diaphana, suggesting that this species is unique among the zooplanktivores – either its ration is three times higher than the other species, or it eats one-third as often (i.e., every 3 days). Given the high percent stomach fullness observed throughout the diel cycle, we believe the former to be the case, which is the first estimate of its kind for a midwater fish. In order to facilitate further quantitative research on mesopelagic carbon cycling, detailed prey length/weight regressions are presented here.